A novel approach for asphaltene inhibitor modeling. (1st February 2016) - Karambeigi, Mohammad Ali; Nikazar, Manouchehr; Kharrat, Riyaz
ABSTRACT: Asphaltenes are typically defined by solubility as benzene soluble and pentane or heptane insoluble. The most common way to asphaltene precipitation reduction is to apply an asphaltene inhibitor. As preliminary trial for inhibitor modeling, some procedures were applied. The most common way is to use known components of inhibitors. Because of some defects in this way, this option was also not adopted. However, simulation software has not included inhibitor option for asphaltene modeling yet. Therefore, we tried to reproduce the effect of inhibitor in this study based on the established models, using commercial inhibitors through the experimental procedure. This study is a new driver for asphaltene inhibitor modeling analysis. The workflow of this method was established by estimating physical properties of the target inhibitor treated as a pseudocomponent, defining the target inhibitor in the base model with the estimated physical properties, drawing ADE on phase diagram, comparing the simulated and experimental ADE diagram, and matching correlations with changing acentric factor.